Efektivitas Game Edukasi Berbantuan Aplikasi Wordwall terhadap Minat Siswa dan Hasil Belajar IPAS Kelas V Sekolah Dasar - Bachrul Ikhsan Avandy; Hera Heru Sri Suryanti; Oka Irmade (Journal on Education, 2024)
This research aims to determine the educational games assisted by wordwall applications is effective on student interest and learning outcomes of IPAS class V SDN Tugu Jebres No.120 in the 2023/2024 academic year. The research approach used is quantitative with the quasi experimental research and non-equivalent control group design. The samples of the research amounted to 41 fifth grade students who were selected through sampling with saturated sampling technique. The data analysis technique was used the Independent Sample Test followed by the N-gain test. The results of the research indicated the effectiveness treatment of educational game assisted by wordwall application, which was obtained in the hypothesis test with a sig. value 0.000 < 0.05 on student learning interest and sig. value 0.002 < 0.05 on learning outcomes. On the basis of the N-gain test, the experimental class learning interest percentage was 57.44% with a quite effective criteria. Meanwhile, the N-gain test on learning outcomes of the experimental class obtained a percentage of 56.96% with a quite effective criteria. So it could be concluded that the treatment of educational games assisted by wordwall application is quite effective on student interest and learning outcomes of IPAS class V SDN Tugu Jebres No.120 in the 2023/2024 academic year.